Governance and Ethical Risk Management Framework for AI-Powered Tax Systems: A Post-Coretax Reform Proposal - Nusivera, Sari (Sahabat Publikasi, 2025)
As artificial intelligence (AI) becomes increasingly integrated into public administration, its adoption within Indonesia’s Coretax system illustrates both transformative potential and pressing governance challenges. This paper investigates Coretax as a case study to explore the ethical, legal, and operational risks of deploying AI in tax administration. While Indonesia’s regulatory framework—especially the Personal Data Protection Law (UU PDP) and SPBE e-government regulations—provides a foundational structure, these alone are insufficient to mitigate risks such as opacity, algorithmic bias, and erosion of public trust. Through qualitative analysis of legal mandates, ethical standards from ACM and OECD, and Coretax’s documented implementation failures, this study proposes a comprehensive Governance and Ethical Risk Management Framework. The framework incorporates impact assessments, an AI oversight board, transparency mechanisms, privacy-by-design architecture, and continuous monitoring. It is designed to ensure legal compliance, ethical accountability, and sustainable innovation in AI-powered public systems. Policy recommendations include mandating AI impact assessments, enhancing legal oversight, updating SPBE guidelines, and investing in AI governance capacity. By implementing this framework, Indonesia can lead in building trustworthy digital government systems—balancing efficiency with fairness, and innovation with the protection of citizens’ rights. The findings offer actionable guidance for policymakers navigating AI integration in high-stakes public services.